Promoting the Children Rights in the media: the important contribution of school newspapers - Tomé, V.; Ponte, C.; Helena Menezes (Human Rights and Citizenship Education - Proceedings of the eleventh Conference of the Children’s Identity and Citizenship in Europe Thematic Network, 2009)
This paper deals with the difficulties globalization brought in terms of two fundamental rights foreseen in the Convention on the Rights of the Child: freedom of expression and image protection in the media. It tries to answer these difficulties and to explain that media have a fundamental role to perform. School can also contribute to overcome these difficulties, promoting those rights through Media Education and newspaper production either printed or online. This proposal is within the scope of a research conducted in Portugal since 2005 and that is nowadays within a research project ‘Media Education in Castelo Branco’ (2007-2010).